Tax Law Design and Drafting, Volume 2 - Thuronyi, Victor (International Monetary Fund, 1998)
A comprehensive guide to income tax legislation, this book is the second of two volumes dealing with tax legislation from a comparative law perspective. Distilled from the IMF Legal Department's extensive experience, the book covers a wide range of issues in both domestic and international taxation. It also includes the most extensive bibliography currently available of the national tax laws of IMF member countries.